Rekonstruksi RUU PPRT Sebagai Upaya Perlindungan Hukum Dalam Penanggulangan Kekerasan Terhadap PRT Perempuan dan Anak - Parvez, Abel; Superani, Andi Vallian; Juaningsih, Imas Novita (Universitas Negeri Semarang in collaboration with Ikatan Penulis Mahasiswa Hukum Indonesia, 2022)
Law protection on domestic worker is one of occupation that woman and children do where in the implementation they must get protection from government since the constitution has guarantee certainty, equality, and protection for every citizen without exception to include them. Government as facilitator in private realm must take responsibility to protect woman and child domestic worker with formulate comprehensive regulation and the institution that carry on in order to shape socio-culture of people to friendly domestic worker. Unfortunately, statutory are not accommodate legal protection for domestic worker. The only hope right now is on department ordinance that still have problem such as contradiction. Based on those problem, the reconstruction of law to solve substantial, structure, and cultural are needed. This research is use statutory approach, comparation approach, and conceptual approach as the method. The conclusion that this research got is the absent of comprehensive legal protection for domestic worker is caused by no legal recognition can give them certainty and protection. Therefore, the initiation to reconstruct protection for domestic worker with the basis is draft act protection for domestic worker that emulate Philippines statutory named Batas Kasambahay and creation of special inspector team for domestic worker are needed.